An analysis of the Notre Dame Educational Association achievement test in Physics - Seneriches, Nasie M. (Animo Repository, 1984)
This study analyzes and interprets the Notre Dame Educational Association (NDEA) achievement test in physics for high school.The subjects were 400 graduating high school students of the eight Notre Dame schools in South Cotabato.On the basis of responses of the examinees, the following were computed: discrimination index, difficulty index, attractiveness of the options and Kuder-Richardson Formula 20 reliability coefficient.For examining the structural characteristics of the items, the classification scheme included the following three areas: knowledge, comprehension, and application.To test the concurrent validity, Pearson product-moment correlation coefficient was calculated between achievement test scores and the students grade point averages in physics.The following conclusions were made:1. There is a need to revise forty-three (43) items or 71.67 percent of the total number of test items.2. While the instrument was found to be reliable, the test has too many (51.67 percent) items testing for knowledge, only 21.67 percent testing for comprehension, and 26.67 percent testing for application.3. The relationship between achievement test scores and the grade point averages in physics is significant at 0.01 level of confidence.On the basis of the information obtained from this study, the following recommendations are hereby suggested.1. The NDEA should form a Committee to make the final revision of the test with a well-trained consultant.2. Revised version of the test should be subjected to further content analysis. 3. The NDEA should construct or develop more physics achievement test of parallel for to safeguard the reliability of the said test.The NDEA achievement test on other subject areas should be subjected to item analysis. There is a possibility that further improvement can be done on those test.